Síntese de novos isoxazóis e pirazóis a partir de derivados 1,3-diíno indólicos - Bassaco, Mariana Moro (2015)
In this work it describe the synthesis and characterization of new 1,3-diynes indole derivatives, the 1,6-bis(1H-indol-1-yl)hexa-2,4-diynes (6 examples) and unsymmetrical 1-(5-arylpenta-2,4-diynyl)-1H-indoles (6 examples), which were obtained in yields between 60 and 85% by homo- and heterocoupling reactions from N-propargyl indolic precursors, derivative from 1H-indole, 5-methoxy-1H-indole, 5-bromo-1H-indole, 2-methyl-1H-indole, 5- (p-tolyl)-1H-indole and carbazole. Subsequently, methodologies were provided for the synthesis of novel isoxazoles (12 examples), 1H-pyrazoles (12 examples) and 1-aryl-1H-pyrazoles (14 examples) by hydroamination reaction between the previously synthesized 1,3-diynes and hydroxylamine, hydrazine and aryl hydrazines, respectively. This synthesis proved to be efficient and clean, since it is free from catalysts and using PEG 400 as the solvent. For each series of compounds, the synthesis was optimized and full the examples were characterized. All products were obtained with high selectivity and yields from 58 to 89% for isoxazoles, 68 to 96% for 1H-pyrazoles and 50 to 75% for the 1-aryl-1H-pyrazoles.